Geometrical integrity of microholes drilled by conventional and micro electrical discharge machining - Ali, Mohammad Yeakub; Rosfazila, M. R.; Rosnita, E. (CSREA Press, 2008)
This paper discusses the comparison of geometrical integrity of microholes drilled by conventional and micro electrical discharge machining (EDM). The microholes were produced on beryllium copper alloy using tungsten carbide electrode of 500 μm diameter. The geometry and surface texture of the microholes were investigated using scanning electron microscope (SEM) and surface profiler. The selected characteristics of geometrical integrity roundness, diameter enlargement, and taper angle were investigated and compared for microholes of different aspect ratios. The trend of geometrical characteristics were established for both conventional and micro EDM.